1997
DOI: 10.1046/j.1365-2125.1997.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin pharmacokinetics following administration of capsules and Neoral in paediatric patients with lupus nephritis

Abstract: Aims Neoral is a new microemulsion form of cyclosporin. Pharmacokinetic reports in children are scarce. Therefore, we performed a pharmacokinetic study between Cyclosporin A (CsA) capsules and Neoral in paediatric patients with lupus nephritis. Methods A single 5 mg kg−1 dose orally of either CsA capsules or Neoral was given to 10 paediatric patients (serum creatinine<1.5 mg dl−1 ). CsA whole blood levels were measured for 24 h post‐dose by h.p.l.c. Results Neoral had a higher Cmax and AUC(Cmax: 943±176 ng ml−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…The pharmacokinetic profile seems to be more stable in individual patients and the interpatient variability is decreased with Neoral as compared to Sandimmun. The results obtained in the present study in stable pediatric patients with steroid-dependent nephrotic syndrome are comparable to those obtained in stable pediatric patients with renal or liver transplants, as well as in patients with systemic lupus erythematosus [1][2][3][4]. In these studies, the use of Neoral results in an earlier peak concentration, with a higher Cmax and a higher AUC, while the trough levels are similar with both formulations.…”
Section: Methodssupporting
confidence: 84%
“…The pharmacokinetic profile seems to be more stable in individual patients and the interpatient variability is decreased with Neoral as compared to Sandimmun. The results obtained in the present study in stable pediatric patients with steroid-dependent nephrotic syndrome are comparable to those obtained in stable pediatric patients with renal or liver transplants, as well as in patients with systemic lupus erythematosus [1][2][3][4]. In these studies, the use of Neoral results in an earlier peak concentration, with a higher Cmax and a higher AUC, while the trough levels are similar with both formulations.…”
Section: Methodssupporting
confidence: 84%
“…Table provides the tabulation of the reported C max and AUC values from the various patient studies and healthy subject clinical pharmacology studies reported in the literature . The prediction of AUC values for cyclosporine was performed using the regression equation: AUCitaliccyclosporine0.25em=italicCmaxitalicCyclosporine0.25em×0.25em3.99650.25emprefix+384.5 and the appropriate fold differences were computed (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The original corn oil formulations of CsA (Sandimmune) have recently been supplanted by a micro-emulsion formulation (Neoral) [5], which seems to demonstrate greater and more consistent bioavailability [5][6][7][8]. The absorption curves of Neoral differ from those of Sandimmune by an earlier and greater peak concentration, namely shorter T max and higher C max [8][9][10]. In addition, in adults the Neoral concentration-time pharmacokinetic (Pk) curves display less inter-and intra-individual variability as compared to Sandimmune [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%